The Role of Learning Openness in Moderating Tacit Knowledge and Heritage-Based Learning by Doing on Human Resource Productivity in Ulu Belu Coffee - Asmirani, Sri; Khairunnisa, Rizky; Pahlepi, Reza; Afrizal, Afit; Pratama., Reza Hardian (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines the role of learning openness in moderating the relationship between tacit knowledge, learning by doing (heritage learning), and human resource productivity in Ulu Belu coffee MSMEs, Indonesia. Grounded in the Knowledge-Based View and Organizational Learning Theory, this research investigates how experiential and inherited knowledge contribute to workforce productivity within traditional agribusiness settings. A quantitative explanatory approach was employed using survey data collected from 200 coffee MSME actors in Ulu Belu, Lampung. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that tacit knowledge significantly and positively influences human resource productivity. Likewise, learning by doing through intergenerational knowledge transfer significantly enhances productivity. These results confirm that experience-based and socially embedded learning mechanisms remain critical drivers of performance in traditional coffee enterprises. Furthermore, learning openness plays a significant moderating role. It strengthens the relationship between heritage learning and productivity, indicating that openness to new ideas, external collaboration, and technological adoption amplifies the benefits of traditional knowledge transfer. Learning openness also moderates the effect of tacit knowledge on productivity, although the effect size is relatively weaker. This study contributes to the literature by integrating tacit knowledge, heritage learning, and learning openness into a single empirical model within the agribusiness MSME context. Practically, the findings suggest that enhancing learning openness alongside preserving traditional knowledge can improve workforce productivity and sustainability in coffee-based MSMEs.